Effect of Pb2+ Ions on the Mechanical, Structural and Thermal Behaviour of B2O3-CaO Glasses - Subashini, C.; Pavai, R. Ezhil; Balu, L. (Asian Journal of Chemistry, 2019)
B2O3-CaO-PbO glasses with different concentrations of PbO (5-20 mol % in four steps) were prepared by melt quench technique. The amorphous nature and homogeneities of the prepared glasses were confirmed by XRD and SEM analyses. Ultrasonic velocities and density were measured at 303 K using pulse-echo technique and Archimedes’ principle respectively. Various parameters, viz., molar volume, longitudinal modulus, shear modulus, bulk modulus, Young’s modulus, Poisson’s ratio, micro-hardness and Debye temperature have been evaluated from the measured data. The results of ultrasonic properties indicate that the incorporation of lead ions expand the calcium borate network structure. FTIR spectra revealed that boron exists in both trigonal and tetrahedral structural units and no boroxial ring formation takes place in the glass structure. The transition temperature, melting temperature and crystallization temperature have been identified using DTA measurements.